THE FACTOR OF LACK OF THE MOTIVATION - Narbekov, Farhod Nuriddinovich (INTERNATIONAL CONFERENCES, 2023)
This article deals with sharing some useful and specific information about some environmental and teacher-related problems that learners faced in a learning environment. These problems lowered their motivation and thus they could not understand the given instructions.